Analisis Rumah Panggung yang ada di Pasar Lama, Meral Kota, Karimun - Yessy Christanti Silaban; Yoseph Seno Prakoso; Antony Antony; Friendy Friendy (Journal of Architectural Design and Development (JAD), 2021)
Coastal settlements are one type of unique area that requires a special approach in understanding its characteristics. So far, coastal settlements in Indonesia are generally known to have very fast and dynamic developments, one of which is the high rate of migrant migration, including in the case study area of ​​Meral Kota. The concept of settlement development is often unsuccessful in its implementation due to a lack of understanding of the characteristics of settlement development patterns so that a special approach is needed in its study. Meral Kota is one of the coastal settlement areas designated as a minapolitan area in Karimun Regency and like coastal settlements in general, this area has a vital role in economic activities because the integration of settlement and economic functions is an existing culture and characteristic. This article aims to analyze the Stage House in the Old Market, Meral City, Karimun. The discussion focused on the Qualitative Method approach and its combination with several other methods.